The Effectiveness of Al-Qur'an Murottal and Effleurage Massage Using Jitu Oil by Breastfeeding Grandmothers on Mother's Confidence in the First Month of Birth - Ningsih, Dewi Andariya; Oktavia, Liana Devi (International Journal of Public Health Excellence (IJPHE), 2024)
Mothers' confidence in providing breast milk to babies is positively associated with increasing breastfeeding duration in various cultures and age groups. It's just that most breastfeeding mothers who are giving birth for the first time feel less confident so that breast milk doesn't flow smoothly. So it requires family support close to the mother, namely the grandmother. Smooth breastfeeding occurs if the mother is relaxed and comfortable. This comfort can be achieved by massage effuerage and listening to murottal Al-Qur'an. The design carried out in this research was a quasi-experiment using a one test only design. This research was conducted in the Arjasa Community Health Center Work Area, Situbondo Regency. The research was conducted in December 2023 - February 2024. The population in this study was post partum mothers who were in the TPMB working area of ​​the Arjasa Health Center. The sampling technique used in this research was purposive sampling. Interpretation of Friedman Test Results on the Effectiveness of Murottal Al-Qur'an and Effleurage Massage Using Jitu Oil by Breastfeeding Grandmothers on the Independence of Breastfeeding Mothers. Descriptive statistics on 41 respondents whose data was collected 7 times in 1 month, namely day 1, day 5, day 10, day 15, day 20, day 25, and day 30 it can be seen that the average level of independence during treatment has increased successively. This research reveals the importance of involving family members, in this case grandmothers, in the context of caring for the mother of the baby, because in this cultural environment, there seems to be a value on the bonds that exist between these women, which benefits the family. intergenerational transmission of knowledge, experience and insight.